2013
DOI: 10.5551/jat.18002
|View full text |Cite
|
Sign up to set email alerts
|

Eicosapentaenoic Acid (EPA) Reduces Cardiovascular Events: Relationship with the EPA/Arachidonic Acid Ratio

Abstract: The clinical efficacy of fish oil and high-purity eicosapentaenoic acid ethyl ester (hp-EPA-E) for treating cardiovascular disease (CVD) has been reported. Fish oil contains saturated and monounsaturated fatty acids that have pharmacological effects opposite to those of ω3 fatty acids (ω3). Moreover, ω3, such as EPA and docosahexaenoic acid (DHA), do not necessarily have the same metabolic and biological actions. This has obscured the clinical efficacy of ω3. Recently, the Japan EPA Lipid Intervention Study (J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
54
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 94 publications
4
54
0
Order By: Relevance
“…Baseline and post-treatment RBC PUFA levels in EMT study participants were similar to those reported previously in studies of omega-3 PUFA supplementation in healthy volunteers [13,19], women with breast hyperplasia [20][21] and in patients with lung cancer [22]. In particular, post-treatment % RBC EPA values were similar to those observed in an eight-week study of exactly the same EPA-FFA formulation and dose in healthy volunteers and inflammatory bowel disease patients [23].…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Baseline and post-treatment RBC PUFA levels in EMT study participants were similar to those reported previously in studies of omega-3 PUFA supplementation in healthy volunteers [13,19], women with breast hyperplasia [20][21] and in patients with lung cancer [22]. In particular, post-treatment % RBC EPA values were similar to those observed in an eight-week study of exactly the same EPA-FFA formulation and dose in healthy volunteers and inflammatory bowel disease patients [23].…”
Section: Discussionsupporting
confidence: 71%
“…Longer-term follow-up would have been required in order to confirm the return of the PUFA profile in RBCs to that observed pre-intervention. 'Washout' kinetics were not dependent on the prior degree of RBC incorporation or duration of EPA treatment and are similar (in these CRC patients) to the decay in RBC EPA content observed in at least three healthy volunteer studies, in which peak RBC EPA content was similar to that seen in the EMT study [13,19,27], as well as two more recent studies of pre-and post-menopausal women [20][21].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…7) It seems therefore likely that in vivo, EPA and DHA exhibit different physiological activities. [8][9][10][11] A strong positive correlation is known to exist between serum EPA and DHA levels, and this was also shown in our study cited above. [4][5][6] Because serum EPA and serum DHA levels serve as confounding factors for each other, there are limits to discussing their effects on the incidence of coronary artery disease.…”
supporting
confidence: 88%
“…12) This result suggests that interventions targeting the serum EPA level or serum EPA/arachidonic acid (AA) ratio could be useful for the prevention of CAD. 11,13) Thus, the n-3/n-6 PUFA ratio may play an important role in reducing the risk of a CV event.…”
mentioning
confidence: 99%